Dramatyzowane homilie patrystyczne zalążkiem dramatu chrześcijańskiego - Longosz, Stanisław (Vox Patrum, 2016)
The author of this paper tries to prove that the origins of Christian drama shouldn’t be sought in Latin liturgical drama crystalized in 9th and 10th century – as it is commonly accepted – but rather much earlier: in Eastern dramatized patristic homilies of 5th, 6th and 7th century. All fully dramatized homilies of those days are arranged in three groups: The homilies about John the Baptist and the Baptism of Jesus Christ; The homilies about descending of Jesus Christ into the abyss and liberation of those who are righteous from hell; Homilies about the Annunciation of Blessed Virgin Mary – most numerous texts. In this article only homilies from group 1 and group 2 are analyzed. The eight most dramatized speeches from these two groups were chosen. From these homilies some fragments or full parts of dialogs are chosen and quoted, as examples of dramatic action, shown in the clearest way (containing the fullness of psychological expression and motion, rhetorically built dialogs of Biblical characters). These parts are explained and commented in the context of the idea of drama proposed by Origen (Commentarius in Cantica Canticorum. Prologus 1, 1-3; I 1, 1-2). From Group 1, the author of this article presents two homilies: Homilia in Sanctam Theophaniam (which authorship is mistakenly assigned to St. Gregory the Wonderworker) and Homilia de baptismo Christi [CPG 5520] of Pseudo- Eusebius of Alexandria. From Group 2 six speeches are chosen. Five of them are written by Pseudo- Eusebius of Alexandria. They make specific cycle, known as Eusebian cycle of descending Christ into the abyss. This cycle – in its contents and structure – is a rhetorical amplification of apocryphal Evangelium Nicodemi (17-27) and Quaestiones S. Bartholomaei Apostoli (I 1-9). These homilies are summarized by the author of this paper. These five Eusebian homilies are completed with well-known Homilia de divini corporis sepultura et de Christi adventu in infernum [CPG 3768] of anonymous author. This last one is quoted on the Holy Saturday in the Liturgy of the Hours (II 386-388). According to some modern authors (i.e. G. La Piana), all these six homilies seem to set up the Christian Passion Drama in three acts (A-C). The structure of this drama is as follows. At the beginning we have well documented theological introduction about descensus in inferos. Then we have three acts with following homilies (first five of them are written by Pseudo-Eusebius of Alexandria): A. Descending of John the Baptist to the abyss to prepare those who are righteous for the coming of Christ: Homilia in illud: „Tu es qui venturus es, an alium exspectamus” [CPG 5521] and Homilia de adventu Joannis in infernum et de ibi inclusis [CPG 5522]; B. The Judas’ betrayal, imprisonment of Jesus and the dread of rulers of the underworld – Satan and Hades – after they have heard about coming of Christ: De proditione Judae [CPG 5523] and Homilia in Diabolum et Hadem [CPG 5524]; C. The Passion and Death of Christ and his descending into the abyss: Homilia de Christi passione [CPG 5526] and Homilia in divini corporis sepultura et de Christi adventu in infernum [CPG 3768]. The numerous and widely presented fragments of dramatized homilies – completed with highly quoted literature of subject – seem to convince clearly, that the origins of Christian drama (reconstructed in unspecified way during the liturgy in the Church) could be reasonably sought as far as in patristic dramatized homily of 6th and 7th century.